More Light Please: Daphnia Benefit From Light Pollution by Increased Tolerance Toward Cyanobacterial Chymotrypsin Inhibitors - Cremer, Ricarda; Wacker, Alexander; Schwarzenberger, Anke (Frontiers in Ecology and Evolution, 2022)
Cryptochromes are evolutionary ancient blue-light photoreceptors that are part of the circadian clock in the nervous system of many organisms. Cryptochromes transfer information of the predominant light regime to the clock which results in the fast adjustment to photoperiod. Therefore, the clock is sensitive to light changes and can be affected by anthropogenic Artificial Light At Night (ALAN). This in turn has consequences for clock associated behavioral processes, e.g., diel vertical migration (DVM) of zooplankton. In freshwater ecosystems, the zooplankton genus Daphnia performs DVM in order to escape optically hunting predators and to avoid UV light. Concomitantly, Daphnia experience circadian changes in food-supply during DVM. Daphnia play the keystone role in the carbon-transfer to the next trophic level. Therefore, the whole ecosystem is affected during the occurrence of cyanobacteria blooms as cyanobacteria reduce food quality due to their production of digestive inhibitors (e.g., protease inhibitors). In other organisms, digestion is linked to the circadian clock. If this is also the case for Daphnia, the expression of protease genes should show a rhythmic expression following circadian expression of clock genes (e.g., cryptochrome 2). We tested this hypothesis and demonstrated that gene expression of the clock and of proteases was affected by ALAN. Contrary to our expectations, the activity of one type of proteases (chymotrypsins) was increased by ALAN. This indicates that higher protease activity might improve the diet utilization. Therefore, we treated D. magna with a chymotrypsin-inhibitor producing cyanobacterium and found that ALAN actually led to an increase in Daphnia’s growth rate in comparison to growth on the same cyanobacterium in control light conditions. We conclude that this increased tolerance to protease inhibitors putatively enables Daphnia populations to better control cyanobacterial blooms that produce chymotrypsin inhibitors in the Anthropocene, which is defined by light pollution and by an increase of cyanobacterial blooms due to eutrophication.